Dept Verse in Surrat Al-Bagarah: Morphological Semantic Study - Al-Maaitah, Mkhled Salman Obid (Journal of Arabic Language Sciences and Literature, 2022)
The Holy Qur’an is replete with innumerable linguistic, grammatical and morphological issues, and with each new study, broad horizons of issues that need study and linguistic tracing emerge as the Holy Qur'an is the inexhaustible miracle of morphological issues, especially when they are related to the Qur’anic context, morphological structures and grammatical structures, loading and semantic structures of words in general, and sources and derivatives in particular. We attempted to address a group of expressions in general, and to study the verse of al-Dain (dept) in a structural, morphological and contextual study, detailing the opinions and sayings of linguists and morphologists in particular, linking them to the occasion of the verse, which is debt and loans, which is the opposite of usury, which God Almighty has prohibited in verses from the same surah. So the lexical and semantic rooting of words was followed, and linked to the context of the topic; objective occasion of the surah, what God Almighty wants to teach us, and the God's verses are still waiting for explanation and clarification; to study their morphological and structural issues; because in the Holy Qur’an there are vast horizons of verbal and structural miracles.
Keywords: Morphological Structures; Loads and Semantics; Morphological Derivatives; Morphological Significance and Context